The Meaning of Online Shopping Behavior in the Perspective of Jean Baudrillard's Social Logic of Consumption: (Case Study in Surabaya City) - Rifqi Khairul Anam; Fareed Ahmad Obaidy (University of Muhammadiyah Malang, 2025)
This study investigates the social meanings and implications of online shopping behavior in Surabaya, Indonesia, a rapidly urbanizing city with high internet penetration and a growing e-commerce sector. It examines how online shopping is experienced and understood by consumers, moving beyond a purely transactional view to explore its role in shaping social relationships, identities, and cultural practices. Using a qualitative approach, the research draws on in-depth interviews with eighteen regular online shoppers in Surabaya, selected through purposive sampling with the assistance of a key informant who owns an online store. The semi-structured interviews explored participants' motivations, purchasing habits, perceptions of online shopping, and the social context of their online consumption. Thematic analysis was employed, involving iterative coding and interpretation of the interview transcripts to identify recurring patterns and key themes. The findings reveal that online shopping in Surabaya is driven by a complex interplay of factors beyond mere convenience. While the ease and efficiency of online platforms are significant motivators, the study highlights the powerful influence of discounts, promotions, and the visual allure of online marketplaces. These factors often lead to impulse purchases and the acquisition of items driven by